Pengaruh Bauran Pemasaran Terhadap Minat Berkunjung Kembali Di Indonesia Science Center - Gunawan, Audy; Dewanta Facrureza (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
This study aims to determine the effect of the service marketing mix (7P) on revisit intention at the Indonesia Science Center. This study uses a quantitative method with a survey approach. The results of the study indicate that simultaneously, the marketing mix variables (7P) have a significant effect on revisit intention. However, partially, only the Price, Place, and Process variables have a positive and significant effect. Meanwhile, the Product, Promotion, Physical Evidence, and Physical Evidence variables do not have a significant effect. This finding indicates that although the overall marketing strategy has an impact on revisit intention, there are still several dimensions that need to be improved to support the overall destination appeal. The conclusion of this study is that the management of the Indonesia Science Center needs to maintain and improve the Price, Place, and Process dimensions that have been proven to be effective in influencing revisit intention. Meanwhile, other dimensions such as Product, Promotion, Physical Evidence, and Physical Evidence require further evaluation and development to increase visitor appeal. Keywords: Indonesia Science Center, Marketing Mix, Revisit Interest.